2013
DOI: 10.1007/s11051-013-1595-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective antibacterial effects of mixed ZnMgO nanoparticles

Abstract: Antibiotic resistance has impelled the research for new agents that can inhibit bacterial growth without showing cytotoxic effects on humans and other species. We describe the synthesis and physicochemical characterization of nanostructured ZnMgO whose antibacterial activity was compared to its pure nano-ZnO and nano-MgO counterparts. Among the three oxides, ZnO nanocrystals—with the length of tetrapod legs about 100 nm and the diameter about 10 nm—were found to be the most effective antibacterial agents since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(77 citation statements)
references
References 21 publications
5
71
0
1
Order By: Relevance
“…Nanocomposites, containing oxides of metal, are of great research interest at the moment due to their high photocatalytic degradation efficiency, sustainable development characteristics, and lack of secondary pollution for water pollution treatment [3,4]. Recently, different types of metal oxide nanocomposites have been synthesized, such as ZnO-Mg [5], CuO/ZnO [6], ZnO-NiO [7], Co 3 O 4 -ZnO [8], and CeO 2 -ZnO [9]. Saravanan et al prepared CuO/ZnO, V 2 O 5 /ZnO, and ZnO/γ-Mn 2 O 3 nanocomposites using the thermal decomposition method [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites, containing oxides of metal, are of great research interest at the moment due to their high photocatalytic degradation efficiency, sustainable development characteristics, and lack of secondary pollution for water pollution treatment [3,4]. Recently, different types of metal oxide nanocomposites have been synthesized, such as ZnO-Mg [5], CuO/ZnO [6], ZnO-NiO [7], Co 3 O 4 -ZnO [8], and CeO 2 -ZnO [9]. Saravanan et al prepared CuO/ZnO, V 2 O 5 /ZnO, and ZnO/γ-Mn 2 O 3 nanocomposites using the thermal decomposition method [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…4 In this respect MgO dissolution and transformation into Mg(OH) 2 brucite represents a prominent system for related investigations since respective insights are also of broader interests for very different fields like the application of refractory materials 9 , passive water treatment 10 , geochemistry and -last but not least -the design of nanomaterials and catalysts. [11][12][13][14][15][16] MgO dissolution processes on well-defined single crystal surfaces have been studied experimentally [17][18][19] and theoretically. [20][21][22] A recent surface science study on the interaction of water with MgO(001) films revealed the emergence of disordered hydroxide surface layers that inhibit the dissolution process at higher pH values.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO NPs have many effects on the great amount of microorganisms including bacteria, fungi, parasites and viruses [13]. Nano-ZnO-inhibited the growth of Bacillus subtilis and E. coli in a concentration-dependent manner, showing complete bacteriocidal effect for concentrations over than 0.1 mg/ml [14]. The IC 50 of ZnO NPs against L. donovani intracellular amastigotes was (0.646), it was lower than those obtained by Delavarim et al [11], which was 37.8 μg/ml for promastigotes of L. major, and higher than those obtained by Enad and Zghair [ 12 ] for L. donovani promastigotes which was 0.…”
Section: Resultsmentioning
confidence: 99%
“…58, No.4C, pp: 2285-2290 2289 attracting attention that the high concentrations show over growth in macrophages [14]. ZnO NPs produce dissolved Zn2+ ions, after then enter the cell and cause production of intracellular Reactive Oxygen Species [15].…”
Section: Salih and Zghairmentioning
confidence: 99%